IDENTIFICATION, QUANTIFICATION AND ANTIOXIDANT ACTIVITY OF SECONDARY METABOLITES IN LEAF AND CALLUS EXTRACTS OF COLEUS FORSKOHLII - K. SUNITHA; K. BHASKARA CHARY; CHETAN C. NIMGULKAR; B. DINESH KUMAR; D. MANOHAR RAO (International Journal of Pharma and Bio Sciences, 2013)
Though sixteen combinations of NAA + BAP, and NAA + KN, used in the study, induced callus from leaves of Coleus forskohlii with a variable response, 0.5mg / l NAA + 1.5mg / l BAP was the most efficient (98.8 ± 1.1). Evaluation of hydro-alcoholic, methanolic and aqueous extracts of leaves and call us for antioxidant activity by DPPH and TBARS methods proved that hydro-alcoholic extracts were more efficient compared to others. Extracts of leaves and callus respectively exhibited IC50 of 63.3µg/ml and 58.5µg/ml by DPPH; while only the callus extract exhibited 60µg/ml by TBARS. Proximity of callus IC50 of 58µg/ml to inhibition concentration indicates higher antioxidant activity compared to leaf extract. Quantification of polyphenols by HPLC exhibited three-fold increase in rosmarinic acid in callus (3.86mg/g), than leaves (1.25mg/g). Higher antioxidant activity of callus, due to rosmarinic acid, directs for further investigation into anti-inflammatory, analgesic and anti- depressant activity.